A Body of Work Standard-Setting Method With Construct Maps. (April 2014) - Wyse, Adam E.; Bunch, Michael B.; Deville, Craig; Viger, Steven G.
This article describes a novel variation of the Body of Work method that uses construct maps to overcome problems of transparency, rater inconsistency, and scores gaps commonly occurring with the Body of Work method. The Body of Work method with construct maps was implemented to set cut-scores for two separate K-12 assessment programs in a large Midwestern state and was compared with a previous standard setting for one of the K-12 assessments programs that used the traditional Body of Work method. Data from the standard settings were used to investigate the procedural, internal, and external validity of the Body of Work method with construct maps. Results suggested that the method had strong procedural, internal, and external validity evidence to support its application.